2016
DOI: 10.3390/ma9121029
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Mortars with Recycled Ceramic Aggregates: Deduction and Prediction of the Stress-Strain

Abstract: The difficult current environmental situation, caused by construction industry residues containing ceramic materials, could be improved by using these materials as recycled aggregates in mortars, with their processing causing a reduction in their use in landfill, contributing to recycling and also minimizing the consumption of virgin materials. Although some research is currently being carried out into recycled mortars, little is known about their stress-strain (σ-ε); therefore, this work will provide the expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
(96 reference statements)
2
18
0
Order By: Relevance
“…Other authors that incorporated recycled ceramic masonry waste as aggregate in mortars also found a decrease in the bulk density of the mortars in the fresh and hardened state [4,11,12,18]. This is explained by the density of RA, which usually is lower than that of the natural aggregate.…”
Section: Bulk Density In Fresh and Hardened Statementioning
confidence: 95%
See 3 more Smart Citations
“…Other authors that incorporated recycled ceramic masonry waste as aggregate in mortars also found a decrease in the bulk density of the mortars in the fresh and hardened state [4,11,12,18]. This is explained by the density of RA, which usually is lower than that of the natural aggregate.…”
Section: Bulk Density In Fresh and Hardened Statementioning
confidence: 95%
“…The incorporation of recycled aggregates in cementitious materials is a possible solution for the disposal of these wastes, replacing the initial constituents and, simultaneously, avoiding landfill deposition of these raw materials. The scientific community has already started researching these applications and their introduction in mortars is growing [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These limits are typical for the upper layer of the improved substrate [41]. Concrete aggregates required preliminary research on saturation in order to prevent the movement of water necessary for hydration [42]. The material did not show any binding properties.…”
Section: Materials Usedmentioning
confidence: 99%